Study on Post-Traumatic Stress Disorder (PTSD) Among Traumatic Amputated Patients Using DSM-5 Revised Criteria - Zahan, Refat; Rahman, Md Abdur; Huda Mamun, Md Shamsul; Ferdaus, Farhana; Akhiruzzaman, -; Yasmin, Rasheda; Shahriah, Sunjida; Islam, Mazharul (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Limb amputation is a common surgical procedure done for therapeutic reasons to prevent further deterioration and save lives. Objective: To assess the level of post-traumatic stress disorder (PTSD) among trauma related amputated patients. Methods: This cross-sectional study was conducted between January and December of 2016 on 296 amputated patients who were admitted in the National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Dhaka, and BDM Hospital and Diagnostic Center, Dhaka, Bangladesh. A semi-structured, questionnaire was developed both English and Bangla (local language) using the variables of the study and validated. Using that tool, face to face interview was taken. The checklists were used to collect their socio-demographic characteristics, information regarding amputation and stress severity and diagnosis of PTSD, collectively termed as DSM-5. Results: Among 296 respondents, 213(72%) were male and 83(28%) were female. The mean age of the respondents was 32.013±5.35 years. PTSD was found in221 (75%), while the rest 75 (25%) had acute traumatic stressdisorder. Among PTSD patients, 10(50%) with digit amputated, 41(68.33%) of upper limb amputated, 155(77.11%) of lower limb amputated, and 15(100%) of both or multiple limbs amputated respondents. 61% had extreme level of stress. PTSD had significant association with sex, age, habitat, occupationposition and part of limb loss (P<0.05). Conclusion: In our country, PTSD is very common in amputated patients and has significant association with sex, age, habitat, occupation as well as part of limb loss. Multidisciplinary team of health professionals should emphasize on the need of amputees, both physically and psychologically and provide an effective rehabilitation plan. International Journal of Human and Health Sciences Vol. 06 No. 02 April’22 Page: 183-187